A hybrid spiral microphone array design for performance and portability. (15th December 2020) - Aldeman, Matthew R.
Abstract: The logarithmic spiral has become a common design archetype for the placement of microphones in microphone array systems. Such designs tend to perform well; however, when the diameter of the array is increased to improve the array's angular resolution, the portability and convenience of the array are significantly compromised. Large spiral-based arrays of more than a few meters in diameter are unwieldy to transport and time-consuming to set up once the array has been transported to the test location. The purpose of this investigation is to serve as a proof of concept to establish the anticipated performance of a new hybrid spiral microphone array. This hybrid microphone array design will combine the portability and convenience benefits of smaller spiral array designs with the performance characteristics of larger arrays. Four modified spiral microphone arrays are proposed. The candidate arrays are constructed by placing microphones exclusively on the axes at the points where the spiral geometries intercept the axes. The resulting arrays are modular, enabling the arrays to be quickly dis-assembled, transported, and re-assembled. The candidate array designs are subjected to a battery of angular resolution testing, and the results are compared with standard existing array designs.